Low PIP4K2B expression in human breast tumors correlates with reduced patient survival: A role for PIP4K2B in the regulation of E-cadherin expression - Keune, Willem-Jan; Sims, Andrew H; Jones, David R; Bultsma, Yvette; Lynch, James T; Jirström, Karin; Landberg, Goran; Divecha, Nullin (Cancer research (Chicago, Ill.), 2013)
Phosphatidylinositol-5-phosphate (PtdIns5P) 4-kinase β (PIP4K2B) directly regulates the levels of two important phosphoinositide second messengers, PtdIns5P and phosphatidylinositol-(4,5)-bisphosphate [PtdIns(4,5)P2]. PIP4K2B has been linked to the regulation of gene transcription, to TP53 and AKT activation, and to the regulation of cellular reactive oxygen accumulation. However, its role in human tumor development and on patient survival is not known. Here, we have interrogated the expression of PIP4K2B in a cohort (489) of patients with breast tumor using immunohistochemical staining and by a meta-analysis of gene expression profiles from 2,999 breast tumors, both with associated clinical outcome data. Low PIP4K2B expression was associated with increased tumor size, high Nottingham histological grade, Ki67 expression, and distant metastasis, whereas high PIP4K2B expression strongly associated with ERBB2 expression. Kaplan-Meier curves showed that both high and low PIP4K2B expression correlated with poorer patient survival compared with intermediate expression. In normal (MCF10A) and tumor (MCF7) breast epithelial cell lines, mimicking low PIP4K2B expression, using short hairpin RNA interference-mediated knockdown, led to a decrease in the transcription and expression of the tumor suppressor protein E-cadherin (CDH1). In MCF10A cells, knockdown of PIP4K2B enhanced TGF-β-induced epithelial to mesenchymal transition (EMT), a process required during the development of metastasis. Analysis of gene expression datasets confirmed the association between low PIP4K2B and low CDH1expression. Decreased CDH1 expression and enhancement of TGF-β-induced EMT by reduced PIP4K2B expression might, in part, explain the association between low PIP4K2B expression and poor patient survival.